2003
DOI: 10.1152/ajpregu.00457.2002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms regulating the marked seasonal variation in melatonin synthesis in the European hamster pineal gland

Abstract: Like many wild species, the European hamster (Cricetus cricetus) adapts to the marked seasonal changes in its environment, namely by hibernation and inhibition of sexual activity in winter. These annual functions are driven by the variation in the environmental factors (light, temperature) that are transmitted to the body through large variations in the duration and amplitude of the nocturnal melatonin rhythm. Here we report that the seasonal variation in melatonin synthesis is mainly driven by arylalkylamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 73 publications
0
21
1
1
Order By: Relevance
“…Understanding the underlying mechanisms involved in this seasonal regulation is difficult because this species is endowed with an endogenous circannual clock (MassonPévet et al, 1994b;Saboureau et al, 1999), and the amount of MEL synthesis appears to be modulated by the external temperature, with lower temperature increasing the MEL peak amplitude (Vivien-Roels et al, 1997). Interestingly, we observed that administration of a ␤-adrenergic agonist during the night in LP augments the low nocturnal level of MEL up to values observed at night in SP (Garidou et al, 2003b). This suggests that the low amplitude of the MEL peak in LP results from a weaker NEergic input from the circadian clock toward the pineal gland.…”
Section: B Variations In the Amplitude Of The Nocturnal Melatonin Peakmentioning
confidence: 63%
See 2 more Smart Citations
“…Understanding the underlying mechanisms involved in this seasonal regulation is difficult because this species is endowed with an endogenous circannual clock (MassonPévet et al, 1994b;Saboureau et al, 1999), and the amount of MEL synthesis appears to be modulated by the external temperature, with lower temperature increasing the MEL peak amplitude (Vivien-Roels et al, 1997). Interestingly, we observed that administration of a ␤-adrenergic agonist during the night in LP augments the low nocturnal level of MEL up to values observed at night in SP (Garidou et al, 2003b). This suggests that the low amplitude of the MEL peak in LP results from a weaker NEergic input from the circadian clock toward the pineal gland.…”
Section: B Variations In the Amplitude Of The Nocturnal Melatonin Peakmentioning
confidence: 63%
“…The amplitude of the nocturnal MEL peak is high from September to April (with a maximum of 10-fold nocturnal increase around November/December) and very low during the summer (with a minimum of a 1.5-fold increase in June; Vivien-Roels et al, 1992, 1997. Interestingly, this photoperiodic variation in MEL peak amplitude is driven by Aa-nat mRNA and AA-NAT activity levels (Garidou et al, 2003b). Similarly, the diurnal levels of 5-ML are the highest in autumn/winter (Vivien- Roels et al, 1992).…”
Section: B Variations In the Amplitude Of The Nocturnal Melatonin Peakmentioning
confidence: 95%
See 1 more Smart Citation
“…The SCN restricts production of melatonin to nighttime by controlling the activity of its rhythm-generating enzyme, arylalkylamine N-acetyltransferase (Aa-nat). In the European hamster, the daily variations of Aa-nat activity result from changes in transcription of the Aa-nat gene (28). Hence, the expression of this gene was used as an index of the pineal gland activation by the SCN.…”
Section: Effect Of Deep Torpor On Circadian Clock-controlled Gene Expmentioning
confidence: 99%
“…Plasma melatonin was analyzed by an RIA previously validated in European hamsters and described in ref. 28.…”
Section: Animalsmentioning
confidence: 99%